Možnosti replikace rozstřikovacích trysek metodou 3D tisku - Petrenec, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2018)
Tato bakalářská práce se zabývá možností použití aditivních technologií (AT) při výrobě tlakových vířivých trysek, za účelem snížení finančních nákladů stejně jako výrobních časů dosahovaných stávajícími metodami výroby. Zadáním stanovuje několik cílů. Konkrétně byly detailně rozebrány jednotlivé metody 3D tisku, představen pro účely práce vybraný typ rozstřikovací trysky společně s požadavky na něj kladenými. Dále byla vyhodnocena použitelnost jednotlivých zástupců AT a také provedeno jejich srovnání. Výsledkem práce jsou dvě potencionálně použitelné metody pro replikaci tlakových vířivých trysek, a to Micro Laser Sintering a Direct Metal Laser Sintering. Z časových důvodů a již tak velkého rozsahu práce, nebyl proveden volitelný 6. úkol a experimentální ověření touto prací stanovených závěrů zůstává otázkou pro další studie.

This bachelor thesis deals with the possibilities of using additive manufacturing (AM) in case of replication of pressure swirl atomizers in order to reduce the financial costs as well as the production times achieved by the existing production processes. Several goals were set by an assignment of this thesis. In particular, the individual 3D printing methods were discussed in detail and the specific selected type of spray nozzle was introduced, together with their requirements that have been elaborated in detail. The applicability of the individual representatives of AM was also evaluated, and their comparison was made. The result of this work are two potentially useful methods for replicating pressure swirl nozzles, namely Micro Laser Sintering and Direct Metal Laser Sintering. Due to lack of time and the already large extent of this thesis, an optional 6th task was not carried out and the experimental verification of these set conclusions remains a question for further studies.
Possibilities for replication of spraying nozzles by means of 3D printing methods
Keywords: 3D tisk; additive manufacturing; tlaková vířivá tryska; Micro Laser Sintering; Direct Metal Laser Sintering; 3D print; additive manufacturing; pressure swirl atomizer; Micro Laser Sintering; Direct Metal Laser Sintering